Exploring Moral Values: Readers’ Responses to the Holocaust in The Boy in the Striped Pyjamas - Rahmatika, Tiara Alifia; Datau, Rizal Octofianto; Rosyidah, Usma Nur Dian (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
The Holocaust is one of the dark events in history that must be remembered. There are many works in contemporary culture or even literature that apply the Holocaust theme. Unfortunately, these works make the sensitive part of this dark history deviate from the truth, which is crucial for the generation who learn about the Holocaust. Therefore, this research examined a novel with a holocaust theme titled The Boy in the Striped Pyjamas by John Boyne. This novel is one of the novels that has become a reference for many people who want to know about the Holocaust and has even been used as learning material for young students yet received many harsh criticisms such as historical inaccuracy even though this novel is considered historical fiction. Thus, it is necessary to study this novel further in order not to mislead the readers. This research will examine readers' reviews on the GoodReads online platform. Because now is the digital era, many people are doing online reading activities and writing reviews on this platform. Analyzing reader reviews also determines the quality of the novel itself. This research will also use the transactional reader response theory by Louise Rosenblatt. Therefore, it shows how changes in meaning occur between the text and the reader's perception.